Silius Italicus' Punica 17.341-654: a literary commentary - Roumpou, Angeliki Nektaria (2019)
This commentary, the first detailed commentary on book 17 in any language, explores the way Silius places himself within the extensive and established epic tradition and the closural methods he uses as he brings his epic to an end. It includes a comprehensive introduction to the poem’s literary and historical context, along with the Latin text, English translation, and a line-by-line commentary that illuminates historiographical, textual, linguistic and literary issues arising from the narrative. More specifically, the second half of book 17 allows for a detailed examination of the final confrontation between Hannibal and Scipio in Zama, Rome’s most glorious victory over an external enemy which mirrors book 9, Rome’s most notorious defeat by the same external enemy. Moreover, Scipio’s triumphant procession in Rome, the Punica’s closing episode, allows for a detailed study of the triumphal closure of the Punica which however, if viewed through Lucan’s Pharsalia, reveals Silius’ scepticism on the nature of imperial power and the domination of the individual over the destiny of a country. While the commentary addresses a broad range of linguistic, thematic, and cultural topics, the thesis also includes a substantial introduction that discusses broader literary issues: Silius’ sources, the divine apparatus, the interchangeable characters of the two leaders, and the poem’s relation to Silius’ contemporary Flavian world. The final aim of this thesis is to discuss the closure of Silius Italicus’ Punica, the first research that has ever been extensively done on this aspect of Silius’ epic, in order to show the epic’s monumentalising function. More specifically, it will showcase how ekphrasis can work as a closural device by analysing the ekphrastic nature of the two final scenes of the epic: Scipio’s triumph and Hannibal’s image as fugitive. Scipio’s triumph recalls Augustus’ triumph – the “real End” of the Aeneid – and Hannibal’s imago fleeing provides him with a sense of eternal remembrance and monumentality. Through this discussion, I will show the importance of both spectacle and monumentality in Flavian Rome and also Silius’ desire to demonstrate the Punica’s conception of itself as a literary monument. Finally, Scipio’s quasi-apotheosis at the very end of the epic expresses Silius’ concerns regarding political matters, such as the acquisition of power and the emergence of individualism in Domitianic Rome. Overall, this thesis stands as the first commentary on the final book of the Punica and its closural method as well as the only English translation of this book in nearly eighty years. It is also an invaluable source for those who study the closure of Latin epic, and especially the Aeneid and the Pharsalia, between which the Punica stands intertextually.